2021
DOI: 10.3390/biology10030180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sampling Season and Catching Site (Wild and Aquaculture) on Gut Microbiota Composition and Diversity of Nile Tilapia (Oreochromis niloticus)

Abstract: The gut microbiota of fishes is known to play an essential role in diverse aspects of host biology. The gut microbiota of fish is affected by various environmental parameters, including temperature changes, salinity and diet. Studies of effect of environment on gut microbiota enables to have a further understanding of what comprises a healthy microbiota under different environmental conditions. However, there is insufficient understanding regarding the effects of sampling season and catching site (wild and aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…These findings would therefore demonstrate a certain degree of resistance in the gut microbiome community of Nile tilapia in response to a single OTC exposure, and agree with a similar study in this fish species [17]. The microbiomes of both baseline and post-OTC treated fish in this study were dominated by Fusobacteria, supporting previous findings that members of this phylum are conserved in fish species, where they play a role in vitamin production for the fish host [19,25,[42][43][44]. Resilience and enrichment in Fusobacteria following antibiotic treatment has been reported in zebrafish (Danio rerio) when exposed to OTC at similar or lower levels, respectively [45,46].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings would therefore demonstrate a certain degree of resistance in the gut microbiome community of Nile tilapia in response to a single OTC exposure, and agree with a similar study in this fish species [17]. The microbiomes of both baseline and post-OTC treated fish in this study were dominated by Fusobacteria, supporting previous findings that members of this phylum are conserved in fish species, where they play a role in vitamin production for the fish host [19,25,[42][43][44]. Resilience and enrichment in Fusobacteria following antibiotic treatment has been reported in zebrafish (Danio rerio) when exposed to OTC at similar or lower levels, respectively [45,46].…”
Section: Discussionsupporting
confidence: 92%
“…The gastrointestinal tract of Nile tilapia is colonised by a community of microorganisms or "microbiome", comprised predominantly of Fusobacteria, Firmicutes, and Proteobacteria [19,20]. In this fish species, gut microbiome members play a pivotal role in supporting host physiology and health, through microbial-mediated functions involved in disease resistance, growth, and metabolism [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, Firmicutes was the most abundant phylum in the Lake Awassa and Lake Chamo samples, whereas Fusobacteriota was the dominant phylum in the samples of Lake Hashengie and Lake Tana. Previous studies on the intestinal microbial communities of Nile tilapia from Ethiopian lakes showed dominance by the phylum Firmicutes followed by Fusobacteriota [15,39]. Fusobacteriota was also reported as a dominant phylum from the intestine of Nile tilapia of Lake Nasser in Egypt [40] and captive Nile tilapia [41].…”
Section: Discussionmentioning
confidence: 85%
“…The functions of gut microbial communities depend on their structure, which is in uenced by several host-associated elements, such as genetic makeup, season, stress, and geographical location [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, seasonal fluctuation of water temperature was also found to change the composition of gut microbiota in Nile tilapia. Bereded et al in a recent study demonstrated modifications of both the diversity and composition of gut bacteria with seasonal and spatial variation [69] .…”
Section: Discussionmentioning
confidence: 99%